How to look expensive : a beauty editor's secrets to getting gorgeous without breaking the bank - Lustig, Andrea Pomerantz (Gotham Books, 2012)
"Glamour's "Beauty Sleuth" reveals tricks of the trade to help you look fabulously high-end -- in any economy. Andrea Pomerantz Lustig has spent twenty years as a beauty editor, and her contact list is packed with the names of the most exclusive stylists in the business.In How to Look Expensive, she combines her own experience with highly coveted secrets she's learned from the experts to help readers achieve buttery highlights, luminous skin, flawless makeup, and more, all on a budget"--